Pelatihan Media Pembelajaran dengan Ms. Office Power Point bagi Guru SMA IT Plus BAZMA Brilliant Dumai - Erna Alimudin; Tri Yuliati; Nur Budi Nugraha (Politeknik Negeri Cilacap, 2019)
Teachers are currently required to use learning media, in accordance with government regulations. Learning media are used for teaching materials for student learning. Learning evaluation can consist of questions or quizzes using multiple choice quiz. Evaluation of student learning by using learning media is one of the things which teachers of IT PLUS BAZMA Briliant High School. Therefore, STT Dumai held community service for IT PLUS BAZMA Brilliant High School Teachers, namely, Training to Make Multiple Choice Test Using Ms. Office Power Point for IT Plus Bazma Brilliant High School Teachers on Wednesday, January 30, 2018. Training provided for three materials, namely techniques and things to consider in making Power Point, the use of features in Power Point, and make a quiz with Power Point. The training was attended by 19 teachers and held for approximately 2 hours. The training begins with the implementing material ending with practice. The material given by sequence is in accordance with the desired goals, namely making learning material and also student learning.